Short-term safety and immunogenicity of inactivated and peptide-based SARS-CoV-2 vaccines in patients with endocrine-related cancer - Song, Rui; Liu, Li; Pan, Qingbo; Liu, Jin; Tan, Jiahe; Deng, Juan; Deng, Qin; Lin, Zijin; Chen, Min; Peng, Mingli; Ren, Hong; Ming, Jia (Frontiers in Immunology, 2022)
Background The aim of this study was to explore the short-term safety and immunogenicity of inactivated and peptide-based SARS-CoV-2 vaccines in patients with endocrine-related cancer (ER). Methods Eighty-eight patients with ER cancer and 82 healthy controls who had completed a full course of inactivated or peptide-based SARS-CoV-2 vaccines were recruited. Adverse events (AEs) were recorded. Responses to receptor-binding domain IgG antibody (anti-RBD-IgG), neutralizing antibodies (NAbs) and RBD+ memory B cells (MBCs) were evaluated. Results Approximately 26.14% (23/88) of patients with ER cancer reported AEs within 7 days, which was comparable to that reported by healthy controls (24.39%, 20/82). Both the overall seroprevalence of anti-RBD-IgG and NAbs was obviously lower in the cancer group (70.45% vs. 86.59%, P < 0.05; 69.32% vs. 82.93%, P < 0.05, respectively). Anti-RBD-IgG and NAbs titers exhibited similar results, and dropped gradually over time. Patients with ongoing treatment had an attenuated immune response, especially in patients receiving active chemotherapy. The frequency of overall RBD+ MBCs was similar between the two groups, but the percentage of active MBCs was remarkably reduced in patients with ER cancer. Unlike antibody titers, MBCs responses were relatively constant over time. Conclusion Inactivated and peptide-based COVID-19 vaccines were well tolerated, but with lower immunogenicity for ER cancer patients. More intensive antibody monitoring and timely booster immunization is recommended for patients with ER cancer presenting disordered subpopulations of RBD+ MBCs.